2022
DOI: 10.1186/s12877-021-02700-1
|View full text |Cite
|
Sign up to set email alerts
|

National trends in the proportion of in-hospital deaths by cause of death among older adults with long-term care: a nationwide observational study in Japan from 2007 to 2017

Abstract: Background Japan has promoted end-of-life care at home and in long-term care facilities, and the total proportion of in-hospital deaths has decreased recently. However, the difference in trends of in-hospital deaths by the cause of death remains unclear. We investigated the variation in trends of in-hospital deaths among older adults with long-term care from 2007 to 2017, by cause of death and place of care. Methods Using the national long-term car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In fact, in 2005, we observed a decreasing trend in hospital deaths and an inverse increase in home deaths in Japan [ 4 ]. However, previous efforts have revealed that the decreasing trend of hospital deaths differs greatly depending on the cause of death (CoD) [ 5 , 6 ], and the details of this trend need to be examined individually.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in 2005, we observed a decreasing trend in hospital deaths and an inverse increase in home deaths in Japan [ 4 ]. However, previous efforts have revealed that the decreasing trend of hospital deaths differs greatly depending on the cause of death (CoD) [ 5 , 6 ], and the details of this trend need to be examined individually.…”
Section: Introductionmentioning
confidence: 99%
“…However, Japan has a low proportion of in-home or facility deaths compared to Western countries such as Canada, the UK, and the US (Taniguchi et al [13]; National Vital Statistics System, 2020). From a policy perspective, it is essential to understand how to bridge the gap between people's wishes and reality at the end of their lives in LTC settings.…”
Section: Introductionmentioning
confidence: 99%